Interprofessional Collaboration Practice Model in Basic Emergency Neonatal Obstetric Services in Covid-19 Pandemic Era - Sulistyaningsih Sulistyaningsih; Suyani Suyani; Ariska Fauzianty (Universitas Aisyah Pringsewu, 2023)
The Basic Emergency Obstetric Neonatal Service program is an effort to reduce mortality in Indonesia, which involves various professions collaborating. Various studies state that interprofessional collaboration is proven to improve the quality of health services and can prevent medical errors, but little is known about interprofessional collaboration in the PONED era of the Covid-19 pandemic in Indonesia. This study aims to develop an Interprofessional Collaboration Practice (ICP) model in PONED in Puskesmas. This research is qualitative research with an embedded single-case design. Collecting data using observation, in-depth interviews and documentation studies. The main informants are doctors and health workers who provide services in PONED cases at the Sedayu I Health Center Bantul, Yogyakarta Special Region, Indonesia. Supporting informants are patients/families and ambulance drivers. The number of main informants is 17 people, while the supporting informants are 2 people. Data analysis used thematic analysis. The results of this study found four themes: interprofessional collaboration practices, institutional support mechanisms, work culture mechanisms and environmental mechanisms. The three mechanisms are interrelated and affect the effectiveness of interprofessional collaboration practices and the quality of PONED. Abstak: Program pelayanan obstetric neonatal emergensi dasar (PONED) merupakan upaya untuk menurunkan angka kematian di Indonesia, yang melibatkan berbagai profesi untuk berkolaborasi. Berbagai penelitian menyatakan bahwa praktik kolaborasi interprofessional terbukti dapat meningkatkan kualitas pelayanan kesehatan dan dapat mencegah medical error, tetapi sedikit yang diketahui tentang model praktik kolaborasi interprofessional pada PONED era pandemic Covid-19 di Indonesia. Penelitian ini bertujuan untuk mengembangkan model Interprofessional Collaboration Practice (ICP) pada PONED di puskesmas. Penelitian ini merupakan penelitian kualitatif dengan desain embedded single case. Pengumpulan data menggunakan observasi, wawancara mendalam dan studi dokumentasi. Informan utama adalah dokter dan tenaga kesehatan yang memberikan pelayanan dalam kasus PONED di Puskesmas Sedayu I Bantul, Daerah Istimewa Yogyakarta, Indonesia. Informan pendukung adalah pasien/keluarga dan sopir ambulance. Jumlah informan utama 17 orang, sedangkan informan pendukung 2 orang. Analisis data menggunakan analisis tematik. Hasil penelitian ini menemukan empat tema yaitu praktik kolaborasi interprofessional, mekanisme dukungan institusional, mekanisme budaya kerja dan mekanisme lingkungan. Ketiga mekanisme saling berhubungan dan mempengaruhi efektivitas praktik kolaborasi interprofessional dan kualitas PONED.